Pomen higiene rok pri zdravstveni negi bolnika na kronični hemodializi - Oštir, Barbara (Obzornik zdravstvene nege, 2005)
Hospital infections represent a serious problem, in our country and abroad. Inspite of the progress in the field of hospital hygiene in general, the hygiene of hands remains the most important element of the chain of transmission. Hand desinfection is the most effective, the least costly and the quickest solution of the problem. Substitute dialysis treatment present high risk of infection. The goal of the research study was to find out the level of hand hygiene among nurses on the dialysis department. The results revealed poor hand hygiene and inadequate activities. The reasons for this extend from exhaustion to ignorance and distrust in changes. Only a systematicapproach to the problem will bring effective solutions.
Keywords: Cross Infection; Dezinfekcija; Disinfection; Handwashing; hemodializa; Hemodialysis; higiena rok; Infekcija navzkrižna; infekcije; Methicillin Resistance; Meticilinska rezistenca; Nursing; Prevention And Control; Roka, umivanje; Stafilokokne infekcije; Staphylococcal Infections; Staphylococcus Aureus; zdravstvena nega